Kłoskowska i Williams, czyli o pewnej zbieżności w czasie - Kowalewicz, Kazimierz (Kultura i Społeczeństwo, 2011)
The phenomenon of publication, in the same year, of two books having identical titles, is enough to study the theory presented therein. Both books feature the notion of culture, which was broadly elaborated by both authors: Antonina Kłoskowska and Raymond Williams already in their earlier analyses. It turns out, however, that no matter the title of a book interesting to us, culture is tackled differently in both of them. Williams seems to keep using anthropological definition of culture, while Kłoskowska suggests sociological approach. A reflection on culture by the English academic has shaped the character of British cultural studies and their subsequent follow-ups around the world. A question arises, to what extent the sociological approach by Kłoskowska may give impetus to cultural research in Poland, especially when symbolic culture appears beyond the principle of autotelism.